The Impact of Moodle on Scientific Attitudes Skills and Student’s Motivation on Science Learning in Elementary School - Rizki Amalia Nuraini; Sujarwo (Postgraduate, University of Mataram, 2025)
The aim of the study was to determine the effect of LMS Moodle on scientific attitudes and motivation in science lessons for class V at SDN Demangan, to find out differences in scientific attitudes and learning motivation between classes using Moodle LMS and classes using PowerPoint in science lessons for class V at SDN Demangan. The subjects in this study were 44 students in class 5 of SDN Demangan. The research method uses a quasi-experimental design with a non-equivalent control group design. The data analysis technique used is the paired samples t-test and the independent samples t-test. The results showed that there was a significant and positive effect of the use of LMS Moodle and Powerpoint on scientific attitudes and learning motivation of students with the results of the t test analysis respectively of 11.762, 10.283 and 8.047 and 10.109 with the same significance 0.00 < 0.05, there are differences in scientific attitudes and learning motivation between classes using Moodle LMS media and classes using PowerPoint media with a significance level (2-tailed) 0.009 < 0.05.